1994
DOI: 10.2214/ajr.163.2.8037051
|View full text |Cite
|
Sign up to set email alerts
|

Application of wavelet compression to digitized radiographs.

Abstract: OBJECTIVE.Image data compression is an enabling tech-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…The higher the RMSE value the poorer the image quality. 20 The average RMSE was 0.57 at ratio of 4.3, 1.39 at 8.5, 3.34 at 20 and 4.84 at 36.6 and corresponding to the bit rates of 1.85, 0.94, 0.40, and 0.22, respectively. Given that each pixel contains 8 bits of data, the maximum average RMSE at a ratio of 36.6:1 corresponds to a difference of 4.8 of 256 possible values (or 1.87 %).…”
Section: Mean Squared Error and Root Mean Squared Errormentioning
confidence: 88%
“…The higher the RMSE value the poorer the image quality. 20 The average RMSE was 0.57 at ratio of 4.3, 1.39 at 8.5, 3.34 at 20 and 4.84 at 36.6 and corresponding to the bit rates of 1.85, 0.94, 0.40, and 0.22, respectively. Given that each pixel contains 8 bits of data, the maximum average RMSE at a ratio of 36.6:1 corresponds to a difference of 4.8 of 256 possible values (or 1.87 %).…”
Section: Mean Squared Error and Root Mean Squared Errormentioning
confidence: 88%
“…For pixels in the interior of a class, the default orders of the classes. The result is refined iteratively to enhance the spatial connectivity of each class by using the algoof the AR and ARMA models are (3) and (3,10). For the border pixels, the default orders are (2) and (2,5).…”
Section: Fig 2 Illustration Of the Four Neighborhood Patterns Testedmentioning
confidence: 99%
“…For MR images, it has been shown coefficients in a training stage. In order to deal with the nonstationarity of the underlying signal, various adaptive that compression of 7:1 to 10:1 can be tolerated before there is a perceptible loss of quality [10,14], and up to DPCM techniques have been developed, which can in general be classified into two categories. The forward adaptive 20:1 before there is a loss of diagnostic accuracy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated various acceptable compression ratios (the ratio of compressed dataset size: original), some up to 30:1 [2]. One study found that compressing chest X-rays to 40:1 did not significantly affect diagnostic accuracy [3].…”
Section: Introductionmentioning
confidence: 99%